Dictionnaire historique de l'adjectif-adverbe, Volume 1 - Hummel, Martin (2021)
The Historical Dictionary of French Adjective-Adverbs (Dictionnaire historique de l'adjectif-adverbe) documents groups such as couper court, which combine a verb and an adjective with adverbial function. The 2.600 The expressions are classified by alphabetical order, from abaisser bas to voyager propre. The articles contain some 12.000 citations covering the whole history of French.